ADMINISTRATION AND MARKETING OF ANTI-CRISIS MANAGEMENT AT THE DAIRY PLANT AS A STRATEGIC OBJECT DURING THE WARTIME - Natalia Koval; Oksana Kubai; Natalia Germaniuk (Baltic Journal of Economic Studies)
The article conducts an analysis of the distinctive features of marketing management and anti-crisis administration at the dairy plants as strategic objects under martial law. The pivotal challenges confronting dairy enterprises encompass a broad spectrum of issues, including political and economic turbulence, disruption to logistics networks, and shifts in consumer sentiment. The focus of this text is on the necessity of developing effective marketing strategies, adaptive management approaches and digital tools to optimise costs and increase competitiveness. In order to ensure the stability of the enterprise, a number of methods must be employed. These include the diversification of distribution channels, co-operation with local producers, the pursuit of grant financing, the use of CRM systems, and staff support. This study places particular emphasis on the function of state assistance in the post-war recuperation of the industry. This material is relevant for scientists, managers, and specialists involved in survival and business development strategies in crisis conditions. The study analyses the financial condition of the "Khmelnitsky plant dry and skimmed milk "Milk Visit" in 2021–2023, identifying the dynamics of key financial indicators and highlighting factors affecting the enterprise's profitability. The constructed model of paired linear regression confirmed the positive relationship between production volume and net profit, thereby indicating the efficiency of business scaling. Notwithstanding the favourable trends, the company is confronted with challenges pertaining to inadequate liquidity and extraneous risks arising from hostilities. The proposed strategies of crisis management are aimed at increasing financial stability, adapting marketing, product diversification and digital transformation, which are necessary conditions for ensuring the sustainable development of the dairy processing enterprise in a crisis.